Skeletal health in breast cancer survivors. (November 2017) - Bruyère, Olivier; Bergmann, Pierre; Cavalier, Etienne; Gielen, Evelien; Goemaere, Stefan; Kaufman, Jean-Marc; Rozenberg, Serge; Body, Jean-Jacques
Highlights: The introduction of adjuvant therapy for breast cancer can have a negative impact on bone health. Results from observational studies suggest that bone health should be assessed after a diagnosis of breast cancer. Current guidelines need to be updated to take into account the significant protective effects observed in women with either normal or low bone mass. An enhanced risk of fracture in long-term survivors of breast cancer remains under debate. Abstract: Although some risk factors for breast cancer might be protective for osteoporosis, several cross-sectional studies have reported, nevertheless, that patients with breast cancer have a lower bone mass and potentially a higher incidence of fractures than expected. In any case, it appears that patients with breast cancer are not protected from osteoporosis, which provides further support for the recommendation that bone health is assessed after a diagnosis of breast cancer. Most adjuvant therapies will lead to increased bone loss and a higher fracture rate. Among the adjuvant therapy options for premenopausal patients with breast cancer, endocrine therapy (ovarian suppression) and chemotherapy can result in cancer treatment-induced bone loss (CTIBL) of up to 10% at the lumbar spine after one year. Antiresorptive therapies prevent CTIBL in premenopausal women with breast cancer. Most of the evidence demonstrating the efficacy of bisphosphonates in the prevention of CTIBL is derived from clinical trials with zoledronic acid. The addition of zoledronic acid 4 mg per six months to adjuvant endocrine therapy maintained and even increased bone mass during a 3-year treatment period and significantly improved disease-free survival in a population of young women who underwent menopause due to the adjuvant treatment. The major contributor to bone loss in the adjuvant treatment of breast cancer in postmenopausal women is the use of aromatase inhibitors (AIs). Oncology trials have underestimated the fracture risk in the setting of AI-induced bone loss. In the ABCSG-18 study, the only trial in which fracture incidence was the primary endpoint, the rate of clinical fractures was close to 10% after 3 years in the placebo group on AIs only. Bisphosphonates and denosumab at osteoporosis treatment doses can counteract AI-induced bone loss. In the ABCSG-18 trial, treatment with denosumab 60 mg injection every 6 months reduced the risk of first clinical fracture relative to placebo by 50%. Current guidelines recommend antiresorptive therapy in patients with a baseline T score of <−2.0 or with two or more clinical risk factors for fracture. These recent guidelines will need to be updated, as similar significant protective effects were seen in women with either normal or low bone mass. Moreover, a formal meta-analysis of individual patient data from more than 18, 000 women in 26 randomized trials of adjuvant zoledronic acid or clodronate treatment for early breast cancer revealed that bisphosphonates significantly reduced the risk of first distant recurrence in bone and the risk of breast cancer mortality, at least in postmenopausal women. Even though the increased risk of fracture during adjuvant treatment for breast cancer in postmenopausal women is notable, an enhanced risk of fracture in long-term survivors of breast cancer remains under debate. The most recent studies suggest that Caucasian breast cancer survivors do not have a significantly increased risk of osteoporotic fracture over the long term.